Influence of Particle Size of Deproteinized Bovine Bone Mineral on New Bone Formation and Implant Stability after Simultaneous Sinus Floor Elevation: A Histomorphometric Study in Minipigs. (23rd June 2013) - Jensen, Simon S.; Aaboe, Merete; Janner, Simone F. M.; Saulacic, Nikola; Bornstein, Michael M.; Bosshardt, Dieter D.; Buser, Daniel
Abstract Background Deproteinized bovine bone mineral (DBBM) is one of the best‐documented bone substitute materials for sinus floor elevation (SFE). Purpose DBBM is available in two particle sizes. Large particles are believed to facilitate improved neoangiogenesis compared with small ones. However, their impact on the rate of new bone formation, osteoconduction, and DBBM degradation has never been reported. In addition, the implant stability quotient (ISQ) has never been correlated to bone‐to‐implant contact (BIC) after SFE with simultaneous implant placement. Materials and Methods Bilateral SFE with simultaneous implant placement was performed in 10 Göttingen minipigs. The two sides were randomized to receive large or small particle size DBBM. Two groups of 5 minipigs healed for 6 and 12 weeks, respectively. ISQ was recorded immediately after implant placement and at sacrifice. Qualitative histological differences were described and bone formation, DBBM degradation, BIC and bone‐to‐DBBM contact (osteoconduction) were quantified histomorphometrically. Results DBBM particle size had no qualitative or quantitative impact on the amount of newly formed bone, DBBM degradation, or BIC for either of the healing periods (p > 0.05). Small‐size DBBM showed higher osteoconduction after 6 weeks than large‐size DBBM (p < 0.001). After 12 weeks this difference was compensated. There was no significant correlation between BIC and ISQ. Conclusion Small and large particle sizes were equally predictable when DBBM was used for SFE with simultaneous implant placement.